Management of patients with liver derangement during the COVID-19 pandemic: an Asia-Pacific position statement. (August 2020) - Wong, Grace Lai-Hung; Wong, Vincent Wai-Sun; Thompson, Alex; Jia, Jidong; Hou, Jinlin; Lesmana, Cosmas Rinaldi Adithya; Susilo, Adityo; Tanaka, Yasuhito; Chan, Wah-Kheong; Gane, Ed; Ong-Go, Arlinking K; Lim, Seng-Gee; et al.
Summary: The COVID-19 pandemic has spread rapidly worldwide. It is common to encounter patients with COVID-19 with abnormal liver function, either in the form of hepatitis, cholestasis, or both. The clinical implications of liver derangement might be variable in different clinical scenarios. With growing evidence of its clinical significance, it would be clinically helpful to provide practice recommendations for various common clinical scenarios of liver derangement during the COVID-19 pandemic. The Asia-Pacific Working Group for Liver Derangement during the COVID-19 Pandemic was formed to systematically review the literature with special focus on the clinical management of patients who have been or who are at risk of developing liver derangement during this pandemic. Clinical scenarios covering the use of pharmacological treatment for COVID-19 in the case of liver derangement, and assessment and management of patients with chronic hepatitis B or hepatitis C, non-alcoholic fatty liver disease, liver cirrhosis, and liver transplantation during the pandemic are discussed.